Unveiling the Mineral and Sugar Richness of Moroccan Honeys: A Study of Botanical Origins and Quality Indicators - Azzedine Abeslami; Hammadi El Farissi; Francesco Cacciola; Ali El Bachiri; Mariane Sindic; Marie-Laure Fauconnier; Etienne Bruneau; Abdelmonaem Talhaoui (Molecules)
This study comprehensively analyzes the mineral and heavy metal profiles of seven honey types, focusing on the contents of potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), cadmium (Cd), and lead (Pb), with particular emphasis on honey produced in eastern Morocco. Multifloral honey was found to have the highest total mineral content (661 mg/kg), while rosemary honey had the lowest (201.31 mg/kg), revealing the strong influence of floral and botanical origin. Darker honey, such as multifloral and jujube, were richer in minerals, with potassium consistently being the most abundant, followed by calcium, magnesium, and iron, while cadmium and lead remained within safe, trace-level concentrations. Additionally, sugar profiling showed that all samples contained fructose, glucose, maltose, turanose, erlose, sucrose, and palatinose, with particularly high fructose and glucose contents in multifloral honey. Principal component analysis (PCA) accounted for 75% of the variation and identified three distinct groups of honey based on mineral content multifloral, eucalyptus, and rosemary. Multifloral and eucalyptus honey had higher concentrations of iron, magnesium, and calcium, whereas rosemary honey was richer in zinc and copper. The findings underscore the potential of honey as a marker of environmental quality and suggest that eastern Morocco honey possesses favorable characteristics for national and international commercialization.